Updated nomenclature and taxonomic status of the plants of Bangladesh included in Hook. f., the Flora of British India: Volume-I - Rashid, M. Enamur; Rahman, M. Atiqur (Bangladesh Journal of Plant Taxonomy, 2011)
Sir Joseph Dalton Hooker in his first volume of the Flora of British India includeed a total of 2460 species in 452 genera under 44 natural orders (= families) of which a total of 226 species in 114 genera under 33 natural orders were from the area now in Bangladesh. These taxa are listed with their updated nomenclature and taxonomic status as per ICBN following Cronquist’s system of plant classification. The current number recognized, so far, are 220 species in 131 genera under 44 families. The recorded area in Bangladesh and the name of specimen’s collector, as in Hook.f., are also provided. Keywords: J.D. Hooker; Flora of British India; Bangladesh; Nomenclature; Taxonomic status. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9305 Bangladesh J. Plant Taxon. 18(2): 177-197, 2011 (December)